Parental Involvement in Home Learning and Academic Achievement among Elementary School Students - Atikah, Dzaimatun; Efendi, Arief Hidayat; Sutisno, Aliet Noorhayati (Papanda Publisher, 2025)
Parental involvement in children's education has become a normative expectation in contemporary society, with research demonstrating its significant impact on academic achievement through skill development and motivation enhancement mechanisms. However, limited research has examined the multidimensional nature of parental involvement in Indonesian elementary school contexts, particularly regarding the factors that influence engagement patterns and their relationship with student outcomes. This qualitative study was conducted at SD Negeri 1 Terusan, Indramayu Regency, from April 7-30, 2025, involving 40 participants comprising parents and fourth-grade students. Data were collected through structured questionnaires measuring five dimensions of parental involvement: learning assistance, facility provision, motivation and emotional support, school communication, and learning supervision. Additional documentation supported data triangulation. Analysis followed a systematic three-stage process of data reduction, presentation, and conclusion drawing. Findings revealed that parents excel in providing emotional support and motivation (87-91% participation rates) and direct learning assistance (78-82%), representing the strongest dimensions of involvement. However, significant gaps emerged in school communication (54-76% range) and systematic learning supervision, particularly regarding technology monitoring (63%). Economic factors influenced facility provision, with 32% of families experiencing resource limitations, while 86% of students reported feeling encouraged rather than pressured by parental approaches. The results validate theoretical frameworks emphasizing motivation enhancement while revealing context-specific patterns that challenge simplified interpretations of cultural capital theory. The universal presence of emotional support across socioeconomic strata, contrasted with differentiated material resource access, suggests that Indonesian parents possess educational commitment that transcends immediate economic circumstances. Critical communication gaps between parents and schools represent institutional collaboration challenges requiring systematic intervention strategies.